Social Sector in a Decentralized Economy : India in the Era of Globalization - Chakraborty, Pinaki; Chakraborty, Lekha; Mukherjee, Anit (Delhi: Cambridge University Press, 2016)
The institutions, architecture and the process of decentralization vary widely across countries. These variations have financial as well as redistributive implications when it comes to providing access to basic public services at local levels. This book is an analytical examination of financing and public service delivery challenges in a decentralized framework. In addition it provides critical insights into the effectiveness of public expenditure through benefit incidence analysis of education and healthcare services in India.